2018
DOI: 10.3390/su10103526
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Goals Dilemma of Residential Water Pricing Policy Reform: Increasing Block Tariffs or a Uniform Tariff with Rebate?

Abstract: Water is a basic necessity and its allocation and utilization, especially pricing policies, impose various social, economic, and ecological impacts on social groups. Increasing block tariffs (IBTs) has gained popularity because it is expected to incentivize water conservation while protecting poor people benefiting from the redistribution effects because of its nonlinear tariff structure. However, it results in price distortion under certain circumstances. Researchers have also proposed an alternative practica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…For example, [50] concluded that Spanish urban water tariffs do not encourage water saving for three main reasons: the fixed fee is usually excessively high, the variable fee is not sufficiently progressive, and the marginal prices are too low. Similarly, [31], analyzing the residential water price reform in a group of cities in China (from uniform to increasing block tariff), conclude that the oversized initial block and the reduced price differentiation between blocks may prevent the reform from being effective as a way to improve water use efficiency and resource conservation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, [50] concluded that Spanish urban water tariffs do not encourage water saving for three main reasons: the fixed fee is usually excessively high, the variable fee is not sufficiently progressive, and the marginal prices are too low. Similarly, [31], analyzing the residential water price reform in a group of cities in China (from uniform to increasing block tariff), conclude that the oversized initial block and the reduced price differentiation between blocks may prevent the reform from being effective as a way to improve water use efficiency and resource conservation.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that the new sanitation fee structure introduced in 2013 was applied equally both for residential and hotel water consumption. While in the case of residential use there is some previous evidence that concludes that the introduction of an increasing block rates system leads to lower levels of water consumption [22,[29][30][31], no such evidence is found in the case of the hotel sector consumption. This study will therefore try to provide new evidence about the effectiveness of a change in water tariff to promote a more conservative use of the resource in the hotel sector.…”
Section: The Water Price Reformmentioning
confidence: 95%
“…Much recent research on demand reduction through pricing, however, often adopts a standard economic approach, notably use of price and income elasticities (e.g., [18,28]). Such understanding is usually necessary, but frequently not sufficient (e.g., [5,29]). For example, prices would need to be set at levels that do not generate very strong resistance, which is not entirely an economic issue.…”
Section: Willingness To Pay For Water In the Kuwaiti Contextmentioning
confidence: 99%
“…Recently a few observers have begun to call for a more sophisticated assessment of water pricing policies for urban areas. Simply pricing for cost recovery and/or for reducing demand may not gain desired results, because there are many non-economic aspects that must be considered, such as perceptions of fairness and equity (e.g., [5]). This research assessed WTP for water using price and two key non-monetary motivations sometimes cited (social/extrinsic and moral/intrinsic), and suggested how such information can be used in developing urban water pricing policy.…”
Section: Conclusion and Future Research Orientationsmentioning
confidence: 99%
See 1 more Smart Citation